Towards meaningful research and engagement: Indigenous knowledge systems and Great Lakes governance - McGregor, Deborah; Latulippe, Nicole; Whitlow, Rod; Gansworth, Kristi Leora; McGregor, Lorrilee; Allen, Stephanie (Osgoode Digital Commons, 2023)
For thousands of years, Indigenous peoples governed their relations in the Great Lakes region, guided by distinct political, legal, governance, and knowledge systems. Despite historic and ongoing exclusion of Indigenous peoples from Great Lakes governance in the Canadian context and other assaults on Indigenous sovereignty, authority, jurisdiction and responsibilities, Indigenous peoples have maintained their relationships with the Great Lakes. In recent years, Indigenous knowledge systems (IKS) have made inroads in Great Lakes governance, thanks primarily to First Nation political advocacy. However, it remains a challenge to include Indigenous knowledge and implement approaches that bridge Indigenous and Western ways of knowing. Instead of asking, ‘‘What needs to be done to support research into Indigenous knowledge systems?”, more appropriate questions addressed in this paper are: ‘‘What needs to be done to support Indigenous peoples to uphold, strengthen, revitalize Indigenous knowledge systems so they are able to share knowledge if they wish?” and ‘‘How can external institutions, agencies, and people engaged in sustainable management of Great Lakes ecosystems better prepare to engage with IKS respectfully and in the manner required by First Nations?”. In this paper, we demonstrate a First Nations-led knowledge sharing approach to research. In addition to making important contributions to Great Lakes governance and to the scientific research landscape in Canada, this paper points to the requirement to support Indigenous research capacity by building the necessary infrastructure and funding to ensure Indigenous people can lead their own research.